2012
DOI: 10.1017/s0021932012000636
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Height and Knee Height in Adolescents in Merida, Mexico, by Head of Household Employment Level and Family Income

Abstract: Variation in height among young adults has been linked to the living conditions of different social groups. The aim of this study was to measure variation in the height and knee height of young adults by head of household employment level and family income. The sample comprised 180 individuals (90 girls) aged 16 and 17 years living in the city of Merida, Mexico. Height and knee height were measured by anthropometry, and individuals' family social and economic data collected from their mothers. Variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previous studies based on the same database reported remarkable association between height and SES in adolescent boys and girls from Merida. [28][29][30][31] Participants representing 2 separate subsamples of 12 to 16 years and 15 to 17 years of age with higher household SES (as determined by proxy indicators including parents' age, education, school types of the participants, monthly household food expenditure) were taller than peers with relatively lower SES. 28,29 In a study among 9-to 17-year old boys and girls, proxy SES indicators were maternal education, school types of participants, household crowding index (number of family members per bedroom), monthly income and employment status (employer, employee, or self-employed), toilet use, and access to potable water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies based on the same database reported remarkable association between height and SES in adolescent boys and girls from Merida. [28][29][30][31] Participants representing 2 separate subsamples of 12 to 16 years and 15 to 17 years of age with higher household SES (as determined by proxy indicators including parents' age, education, school types of the participants, monthly household food expenditure) were taller than peers with relatively lower SES. 28,29 In a study among 9-to 17-year old boys and girls, proxy SES indicators were maternal education, school types of participants, household crowding index (number of family members per bedroom), monthly income and employment status (employer, employee, or self-employed), toilet use, and access to potable water.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little data have been collected on KH and body proportionality in children and adolescents of Maya ancestry on the Yucatan Peninsula. 30,31 The hypothesis of the present study was that existence of differential pubertal growth characteristics of height and KH could identify the contribution of KH to the final or adult height. In the present study, we address the differential timing and tempo of height and KH growth during puberty in a sample of children and adolescents, including some of Mayan ancestry from Merida, Yucatan.…”
Section: Introductionmentioning
confidence: 89%
“…Household crowding is a measure of the conditions experienced by family members and is closely associated with the resources invested by parents in offspring wellbeing. The rationale behind the selection of these variables was based on available data about factors with plausible links to child nutritional status in the local context (Vázquez‐Vázquez et al, ; Vázquez‐Vázquez, Azcorra, Falfán, & Dickinson, ) and on a wider scale (Case, Lubotsky, & Paxson, ; Vázquez‐Nava, Treviño‐Garcia‐Manzo, Vázquez‐Rodríguez, & Vázquez‐Rodríguez, ). The SEI was built by adding socioeconomic variable response categories.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Osteometric studies show that in humans, the lower segment of the leg tends to exhibit more relative variability than the upper segments. In view of the fact that the lower segment of the leg is more sensitive to environmental influences than the upper segment, one would expect the diagnostic efficiency of growth retardation to be greater in the lower segment of the leg than in total leg length or even height (Frisancho, ) (Vázquez‐Vázquez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for the use of relative leg length (leg length relative to height), as an indicator of environmental conditions during infancy and childhood (Bogin & Varela‐Silva, ). Relative leg length has also been proposed as an objective marker of pubertal timing, because the estrogen surge at puberty truncates leg but not torso growth (Bogin & Varela‐Silva, ; Vázquez‐Vázquez, Azcorra, Falfán, & Dickinson, ). Beyond pubertal timing, the relative importance of early‐life growth rate vs prepubertal growth duration in determining relative leg length may be determined by the social and economic context (McIntyre, ).…”
Section: Introductionmentioning
confidence: 99%